PERAN ORANG TUA DALAM MEMBENTUK KARAKTER ANAK DI ERA GLOBALISASI DI DESA MASIGIT KELURAHAN CITANGKIL KOTA CILEGON - Fitria Nuraini; Toni Anwar Mahmud (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2020)
The title of the research is The Role of Parents in Shaping the Character of Children in the Globalization Era in Masigit Village, Citangkil Village, Cilegon City. In the current era of globalization, there are many influences, both positive and negative. This negative influence must be avoided because it can affect a person's habits, attitudes, and behavior. Character education is one of the important things that must be applied in the family environment. Parents must reflect good attitudes and habits in interacting in the family environment and in the community environment. This is important for fostering good attitudes and habits in children. The formulation of the problem in this study is how the role of parents in improving children's character in the era of globalization, Masigit Village, Citangkil Village, Cilegon City. What factors can influence the formation of children's character in the era of globalization, Masigit Village, Citangkil Village, Cilegon City. What efforts are made by parents in shaping children's character in the era of globalization in Masigit Village, Citangkil Village, Cilegon City. This study aims to determine the role of parents in shaping children's character in the era of globalization in Masigit Village, Citangkil Village, Cilegon City. The subjects of this study were 6 parents and 6 children in Masigit Village, Citangkil Village, Cilegon City. This research uses descriptive qualitative research methods. Data analysis in qualitative research is by doing data reduction, data presentation, and data verification. The results of this study indicate that the role of parents in Masigit Village, Citangkil Village, Cilegon City has been good in shaping children's character in the era of globalization.